2018
DOI: 10.1111/apa.14484
|View full text |Cite
|
Sign up to set email alerts
|

Changes in autonomic regulation due to Kangaroo care remain unaffected by using a swaddling device

Abstract: The use of an alternative swaddling device aimed at facilitating Kangaroo care did not enhance autonomic regulation, as measured by vital signs and heart rate variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
(39 reference statements)
3
10
0
Order By: Relevance
“…However, despite adjusting for baseline HRV which already captures the contribution of PMA, during KC, HRV was still affected by the PMA. This finding affirms previous results suggesting that the response to KC is affected by the maturational state of the infant 7,8 . While in the incubator, with increasing PMA, pDec approaches 50% but by performing KC there appears to be further PMA-dependent catalysis that facilitates pDec towards 50%.…”
Section: Discussionsupporting
confidence: 92%
“…However, despite adjusting for baseline HRV which already captures the contribution of PMA, during KC, HRV was still affected by the PMA. This finding affirms previous results suggesting that the response to KC is affected by the maturational state of the infant 7,8 . While in the incubator, with increasing PMA, pDec approaches 50% but by performing KC there appears to be further PMA-dependent catalysis that facilitates pDec towards 50%.…”
Section: Discussionsupporting
confidence: 92%
“…In the research series published by Kommers et al [ 47 , 48 , 49 , 50 ], different results were found. In one study, no statistically significant HRV was reported [ 47 ], and significantly lower HRV was reported in the other two studies [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, analysis of the 22 selected studies revealed that nine studies focused on HRV [ 36 , 38 , 44 , 45 , 46 , 47 , 48 , 50 , 51 ], six studies on stress [ 26 , 36 , 38 , 41 , 54 , 55 ], and nine on cortisol [ 40 , 42 , 43 , 51 , 52 , 54 , 55 , 56 , 57 ], while the remaining six focused on oxytocin [ 40 , 43 , 48 , 53 , 55 , 57 ]. The studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kangaroo mother care method is said to be more effective at increasing the baby's body temperature (Hakimi et al, 2017)compared to the swaddling method which does not have a thermal advantage (Tsogt et al, 2016). The swaddling method can be a follow-up care after the kangaroo mother care method to maintain warmth for low-weight newborns in the community (Kommers et al, 2019) but it cannot increase the baby's body temperature. The two methods have different functions as a treatment for low birth weight newborns as well as the positive effects that are related to increasing and maintaining a stable body temperature of newborns with low weight in the community.…”
mentioning
confidence: 99%